1982
DOI: 10.1007/bf01851193
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Na+ and Ca2+ activities in aortic smooth muscle cells from spontaneously hypertensive rats

Abstract: Elevations of intracellular Na+ and Ca2+ in essential hypertension have up to now only been demonstrated in blood cells. Therefore, intracellular Na+ and Ca2+ activities were determined in cultured aortic smooth muscle cells from nine spontaneously hypertensive rats of the Münster strain and from nine normotensive Wistar rats. Intracellular ion activities were determined by ion-selective electrodes. In muscle cells from spontaneously hypertensive rats intracellular Na+ activity was markedly elevated (P less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…On the whole, the results reported above together with earlier findings [1] suggest the action ofa humoral factor in the spontaneously hypertensive rat. Further investigations are necessary to identify this humoral factor.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…On the whole, the results reported above together with earlier findings [1] suggest the action ofa humoral factor in the spontaneously hypertensive rat. Further investigations are necessary to identify this humoral factor.…”
Section: Discussionsupporting
confidence: 61%
“…It was shown that the changes in intracellular free Ca 2+ and Na +, which can be demonstrated in red blood cells from essentially hypertensive and from spontaneously hypertensive rats, are modified in cultured aortic smooth muscle cells from spontaneously hypertensive rats. Whereas intracellular Na + is more markedly elevated in cultured smooth muscle cells than in red blood cells from spontaneously hypertensive rats, conversely intracellular free Ca 2+ was shown to be not significantly elevated in aortic smooth muscle cells from spontaneously hypertensive rats [1]. With regard to these results the question arises as to what extent the discrepancies to the findings in red blood cells were caused by the absence ofhumoral factors in the culture medium, since the cultured aortic cells have not been exposed to any hormonal factors specific to one of the rat strains in the artificial medium.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Evidence for an inverse correlation of plasma Ca 2+ and blood pressure has been reported in humans 13 and animals. 14 There is evidence for increased Ca 2+ in erythrocytes 15 and platelets of hypertensive humans. 16 Recent data from our laboratory suggest that a differential action of nitrendipine and related dihydropyridines might be found in SHR versus Wistar-Kyoto (WKY) rat vascular muscle because of Ca 2+ channel differences.…”
mentioning
confidence: 98%